Detection of Polychlorinated Biphenyls in the Atlantic Mackerel (Scomber scrombus) Sourced from Cold Storage in Benin City, Nigeria - Oiseoje M. Wangboje; Ruth Idemudia (Department of Aquaculture, 2022)
The aim of this study was to determine the PCB levels in the Atlantic Mackerel (Scomber scrombus) sourced from cold storage points in Benin City, Nigeria by GC analysis and its suitability for human consumption. The PCB concentrations (mg/kg) in S. scombrus ranged from 0.0183 for PCB 114 to 0.5542 for PCB 126 with a recorded total of 0.991 while the mean concentrations (mg/kg) of PCBs in S. scombrus by cold storage point ranged from 0.0111 for PCB 114 to 0.684 for PCB 126 both at the New Benin points, with no observed significant difference (P>0.05) in the mean concentrations of PCBs 126, 156 and 180 in fish between these points. The mean concentration (mg/kg) of PCBs in S. scombrus by month peaked in June with a value of 0.615 for PCB 126. However, there was no observed significant difference (P>0.05) in the mean concentrations of PCBs 114, 118, 138, 153, 156 and 180 in fish specimens between months. Essentially, data from the study revealed that the experimental fish species are suitable to eat by the consuming public as there was no glaring indication of immediate health hazard.